2019
DOI: 10.1093/trstmh/trz071
|View full text |Cite
|
Sign up to set email alerts
|

Inapparent dengue virus infection among students in Mandalay, Myanmar

Abstract: Background A school- and laboratory-based cross-sectional descriptive study was conducted to find out the burden of inapparent dengue virus (DENV) infection in Mandalay where DENV is endemic and there is circulation of all four DENV serotypes. Methods A total of 420 students who had no history of fever and visited the hospital within 6 months were recruited from three monastic schools. Serum samples were collected and the DEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…By using an adjusted odds ratio (aOR), we determined that participants from Myeik (aOR: 1.9, 95% CI: 1.2–3.0) and Yangon (aOR: 2.4, 95% CI: 1.3–4.2) are approximately two times more at risk of CHIKV infection than those from Mandalay. The reason the CHIKV seropositivity rate in Mandalay is lower than the other two cities, despite previous reports of the high endemicity of other arboviruses transmitted by similar vectors, is unclear [ 36 38 , 55 ]. Both IgG and IgM seropositivity were observed at all the study sites, indicating ongoing infection despite previous exposure, and also suggesting that CHIKV endemicity is maintained within the studied regions [ 56 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…By using an adjusted odds ratio (aOR), we determined that participants from Myeik (aOR: 1.9, 95% CI: 1.2–3.0) and Yangon (aOR: 2.4, 95% CI: 1.3–4.2) are approximately two times more at risk of CHIKV infection than those from Mandalay. The reason the CHIKV seropositivity rate in Mandalay is lower than the other two cities, despite previous reports of the high endemicity of other arboviruses transmitted by similar vectors, is unclear [ 36 38 , 55 ]. Both IgG and IgM seropositivity were observed at all the study sites, indicating ongoing infection despite previous exposure, and also suggesting that CHIKV endemicity is maintained within the studied regions [ 56 ].…”
Section: Discussionmentioning
confidence: 96%
“…This study retrospectively analyzed serum samples that had been used in previous research studies [ 36 38 ]. The study population comprised 1,544 healthy volunteers and febrile patients with suspected DENV infection.…”
Section: Methodsmentioning
confidence: 99%
“…It will serve as source of infection through vectors [ 27 ]. One study conducted in Mandalay in 2018, the same period as that of the current study, identified six cases of asymptomatic DENV-1 infected children in Mandalay [ 28 ]. DENV-1 was also the dominant serotype among inapparent DENV infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a more effective vaccine should represent those DENVs actually circulating in endemic areas. Another aspect where false priming might play a role would be priming against DENV by asymptomatic infections [ 32 , 33 ] and traveling between areas where DENVs are antigenically different [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%